COMPACTION CREEP OF QUARTZ SAND AT 400-600°C: EXPERIMENTAL EVIDENCE FOR DISSOLUTION-CONTROLLED PRESSURE SOLUTION - Niemeijer A.R.; Spiers C.J.; Bos B. (My University, 2002)
Intergranular pressure solution (IPS) is an important compaction and deformation mechanism in quartzose rocks, but the kinetics and rate-controlling process remain unclear. The aim of the present study is to test microphysical models for compaction creep by IPS against isostatic hot pressing experiments performed on quartz sand under conditions expected to favor pressure solution (confining pressure 300 MPa, pore water pressure 150-250 MPa, temperature 400-600°C). Microstructural observations revealed widespread intergranular indentation features and confirmed that intergranular pressure solution was indeed the dominant deformation mechanism under the chosen conditions. For porosities down to 15%, the mechanical data agree satisfactorily with a microphysical model incorporating a previously determined kinetic law for dissolution of loose granular quartz, suggesting that the rate-limiting mechanism of IPS was dissolution. The model also predicts IPS rates within one order of magnitude of those measured in previous experiments at 150-350°C, and thus seem robust enough to model sandstone compaction in nature. Such applications may not be straightforward, however, as the present evidence for dissolution control implies that the compositional variability of natural pore fluids may strongly influence IPS rates in sandstones.
Keywords: ROCKS; DEFORMATION; PRESSURE SOLUTION; KINETICS; SANDSTONE; COMPACTION; DIAGENESIS